Message from the CAP 2017 Organizing Committee - Seceleanu, Cristina; Kasahara, Hironori; Seceleanu, Tiberiu (Proceedings - International Computer Software & Applications Conference, 2017)
CAP Introduction. Presents the introductory welcome message from the conference proceedings. May include the conference officers' congratulations to all involved with the conference event and publication of the proceedings record.